2012
DOI: 10.1111/j.1365-2702.2011.03991.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hospital work environment and nurse outcomes in Guangdong, China: a nurse questionnaire survey

Abstract: Aims and objectives This study examines the relationship between hospital work environments and job satisfaction, job-related burnout and intention to leave among nurses in Guangdong province, China. Background The nursing shortage is an urgent global problem and also of concern in China. Studies in Western countries have shown that better work environments are associated with higher nurse satisfaction and lower burnout, thereby improving retention and lowering turnover rates. However, there is little resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
2
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 29 publications
7
122
2
24
Order By: Relevance
“…31,32 This assertion is similar to the findings of many studies. 9,23,24,33,34 This study found high level of burnout among participants who have 1-5 living children. However, the current study did not find any association between the level of burnout and number of living children (P>0.05).…”
Section: Personal Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 This assertion is similar to the findings of many studies. 9,23,24,33,34 This study found high level of burnout among participants who have 1-5 living children. However, the current study did not find any association between the level of burnout and number of living children (P>0.05).…”
Section: Personal Risk Factorsmentioning
confidence: 99%
“…Similar to this, various studies identified high level of burnout among ICU nurses. 3,4,[21][22][23][24][25] However, a census report on risk factors on burnout and fatigue among nurses revealed a low level of burnout (14.5%) in the ICU comparing to other units; oncology 21.9%, theatre 17.2% and 15.9% in the Emergency Department. Therefore, ICU was not proven to be a stressful working environment than other working units.…”
Section: Level Of Burnout Among Icu and Emergency Department Nursesmentioning
confidence: 99%
“…All studies support the possibility that job satisfaction levels could be affected according to the clinical setting. It has also been concluded that by improving the work environment, job dissatisfaction levels have decreased 9 . This in turn influences productivity together with better quality of work within any organization 2 .…”
Section: Contribution Of Work Environment and Settingmentioning
confidence: 99%
“…Positive work environment plays a comprehensive role in order to promote healthy work. Liu et al [8] study on the work environments of hospital nurses in China. "The findings of this study indicated that nurses in nearly 40% of the surveyed units rated their work environments as poor, and nurses were dissatisfied with their job and suffered from high burnout.…”
Section: Strategies To Resolve the Organizational Problem/issuementioning
confidence: 99%